Avaliação de desempenho das estratégias de controle para suavização da potência ativa de sistemas fotovoltaicos com armazenamento de energia - Diaz, Valentin Nicolas Silvera (2019)
Recent technological advances in photovoltaic cells and the involved power electronics have placed photovoltaic solar energy in a prominent position, while still being a clean and economically competitive power generation with market expansion potential. However, photovoltaic generation depends on solar resource availability being directly influenced by irradiance variation due to the presence of clouds under the photovoltaic panel causing a variation of the active power generation. As the share of photovoltaic solar energy in the power grid increases, these fluctuations may affect power quality and system reliability. Therefore, the use of battery energy storage systems (BESS), together with PV, is a technical viable solution to mitigate these power fluctuations below the maximum allowable. Given the above, this dissertation presents the results of the performance analysis of three different smoothing strategies reviewed from the literature. For the performance analysis purposes criteria, such as the storage capacity and the maximum power required by the storage system are used. Additionally, two models estimate battery degradation. The diffused one used in the literature for photovoltaic power smoothing applications: the (i) event-oriented model, and (ii) the semi-empirical equation-weighted load model greater coverage of the stress factors considered. For the validation of the strategies, real PV production data from 1 kWp photovoltaic system and the solarimetric station where installed at Unioeste (Foz do Iguaçu / PR) and where used to feed a photovoltaic plant model and create power profiles for different installed capacity of photovoltaic systems. As a result, simulations shows that, it was found that the relationship between battery requirements, power and capacities is inversely proportional to the size of photovoltaic systems and the maximum allowable fluctuation ramp. Also, according to the analyzes performed it is determined which of the evaluated strategies has the best performance for each compared item. Additionally, the comparison between degradation models has show a difference of at least 17% from the estimated degradation between them, and the value estimated by the event-oriented model always has a smaller degradation.